Relationship between periodontal disease and respiratory conditions in patients admitted to the Internal Medicine ward - Beatriz María Borrell Fuster; Víctor René Navarro Machado; Ana Belkys Hernández Millán; Beatriz María Fuster Cabrera; Belkis Julia León Águila (Medisur)
Foundation: periodontal disease may be a risk factor for respiratory diseases as long as the respiratory tract is in close relation to the oral cavity. Objective: to describe the asossciation between periodontal disease and respiratory diseases. Methods: descriptive, prospective study of series of cases. Universe, admitted patients to the Internal Medicine Service from September 2015 to January 2016, with decompensated acute or chronic respiratory diseases and for more than five days in the service. Each patient underwent a dental examination in the first week after admission. The following variables were analyzed: sex, age, type of observed periodontal disease and respiratory disease that they presented, as well as risk factors. The information was collected through medical records, questionnaire and oral examination. Results: all patients with respiratory disease had some type of injury which included them within any of the periodontal conditions; the most frequent were the formation of bags between 4 and 5 mm (70.3%) and gingival bleeding (33.3%). The predominating risk factor for both groups of diseases was the smoking habit. Conclusion: there is a relationship between acute and chronic decompensated periodontal and respiratory diseases. Both diseases have common risk factors.